Open and Distance eLearning New Dimensions in Teaching, Learning, Research, and Extension for Higher Education Institutions [sample] - Alfonso, Grace Javier (International Journal on Open and Distance e-Learning (IJODeL), 2015)
Abstract Open and Distance eLearning has helped evolve the idea of openness in education which expands to include the following (Alfonso, 2014): Openness in admission policies; openness in credit recognition and accreditation; openness in delivery modes; openness in cost and affordability (some are free); openness in choosing educational track through multiple bridges and pathways, exits and entrances; openness in course design and evaluation; openness in strengthening digital literacies and e-pedagogies, emerging e-Research paradigms. The digitization of open and distance learning led to the Open Educational Resources (OER) movement and popularity of Massive Open Online Courses (MOOCs). Based on UP Open University’s experience in Open and Distance eLearmig (ODeL), new dimensions of openness in instruction, research, and extension are explored, including the use of analytics in research, teaching and learning particularly in the areas of assessment and evaluation; openness in the shift from faculty-centered to learner-centered teaching; openness in flexible, distributed, blended, technology-enhanced and active learning; openness in the use of new digital technologies for course materials and for being in the core of teaching and learning process; openness in sharing resources and linking digital repositories; and openness in the use of Massive Open Online eLearning Systems as free and accessible to all. Keywords: e-learning, open and distance learning, open and distance e-learning